Exploration of key factors in Gingival Crevicular fluids from patients undergoing Periodontally Accelerated Osteogenic Orthodontics (PAOO) using proteome analysis - Jiaqi Wu; Li Xu; Cuiying Li; Xiujing Wang; Jiuhui Jiang (BMC, 2023)
Abstract Background The aims of this study are to explore protein changes in gingival crevicular fluid at different time points after PAOO by proteomics method and to select significant bone metabolization-related biomarkers. Methods This study included 10 adult patients experiencing PAOO. After orthodontic alignment and leveling, the maxillary anterior teeth were treated with PAOO, which is classified as the experimental area. The traditional orthodontic treatment was performed in the mandibular dentition as the control. Gingival crevicular fluid samples were collected at the following time points: the day before the PAOO (T1) and at 1 week, 2 weeks, 1 month, 2 months and 6 months after PAOO (T2, T3, T4, T5 and T6, respectively). The label-free quantitative proteomic assay was used to evaluate the gingival crevicular fluid in PAOO and control areas at time point T1, T2, and T4. Bioinformatics analysis was carried out to categorize proteins based on biological processes, cellular component and molecular function, which is in compliance with gene ontology (GO) standards. The changes of proteins were confirmed by ELISA. Results A total of 134 proteins were selected by keywords (Osteoblast markers, Osteoclast markers, Osteoclastogenesis regulating genes and inflammatory marker). 33 of them were statistically different between groups, and 12 were related to bone metabolism. 5 proteins selected by label-free quantitative proteomics were KLF10, SYT7, APOA1, FBN1 and NOTCH1. KLF10 decreased after PAOO, hitting a trough at T4, and then leveled off. SYT7 increased after PAOO, reaching a peak at T3, and then stabilized until T6. APOA1 ascended to a peak at T4 after PAOO, and then remained stable until T6. The FBN1 rose after PAOO, reaching a peak at T4, and then went down slowly. NOTCH1 ascended rapidly in the first two weeks after PAOO and continued its slow growth trend. Conclusion In this study, protein changes in gingival crevicular fluid were detected by proteomics method, and significant bone metabolization-related proteins were selected. It is speculated that APOA1, FBN1, NOTCH1, SYT7 and KLF10 played key roles in regulating bone metabolic balance and in reversible osteopenia after PAOO, which might be involved in the accelerated tooth movement. Trial registration This study was registered in the Chinese Clinical Trial Registry (Clinical trial registration number: ChiCTR-ONRC-13,004,129) (26/04/2013).